An Integrative Approach in Learning Islamic Religious Education at the Integrated Islamic Elementary School of Muhammadiyah Sindue - masnun, masnun; Pettalongi, Adawiyah; rustina, Rustina (INTERNATIONAL JOURNAL OF CONTEMPORARY ISLAMIC EDUCATION, 2024)
This research aims to understand how integrative strategies are used in Islamic learning at the Integrated Islamic Elementary School of Muhammadiyah Sindue, with a focus on its practical implications. The problem is how to implement an integrative approach, the success of its implementation, and the factors that influence the integrative approach in learning Islamic religion at the Integrated Islamic Elementary School of Muhammadiyah Sindue. This research uses a descriptive, qualitative approach, which describes events and phenomena that occur in the field and presents data systematically, factually, and accurately. Data collection was carried out using observation, interviews, and documentation techniques. The author uses triangulation techniques and sources to check the validity of the research data. Data analysis in this research uses four techniques: data collection, data reduction, data presentation, and conclusion. This research shows no fundamental difference in implementing the teaching and learning process using an integrative strategy with other strategy styles, only that the approach emphasizes applying moral values and different character traits. The teacher's successful implementation of the integrative approach was quite good, and the students' responses were good. The approach was constructive in the process, but there were still obstacles in the learning techniques, which could be seen from the students' responses that had yet to be fully achieved. The factors that influence the implementation of the Integrative Approach, namely the supporting factors, are the response of pretty good students and the teaching staff or, in this case, professional educators. In contrast, the obstacle is the relatively short duration of time, so in the learning process, the application of moral values becomes limited. An Integrative Approach to Learning Islamic Religious Education It is important to apply an approach emphasizing moral values or manners. Students get lessons following the existing curriculum and the bonus of instilling good Islamic values in their lives.